Maps of 2-manifolds into the plane - Prishlyak, A. O.; Bondarenko, A. M. (Methods of Functional Analysis and Topology, 2012)
We define a p-graph and describe how it changes under isotopy of projections for classification of maps of 2-manifolds into plane. The problem of graph implementation and maps classification are considered.